Extractivist Model in Argentina (1990-2016): From Classic Neoliberal Extractivism to Progressive Neo- Extractivism? Three Case Studies - Gómez-Lende Sebastián (Sociedad y Economía, 2019)
According to the literature, the current Latin American neo-extractivist paradigm would differ from the neolib- eral, “classic” extractive pattern due to the lower relative weight of foreign private capital and, consequently, the appropriation by the State of a substantial piece of the surplus through several mechanisms (e.g. normative and institutional reforms, increase of pre-existent taxes, creation of public enterprises, imposing export taxes, etc.). This paper critically examines such claims and empirically contrasts them for the Argentinean case by analyzing three sectors: agribusiness, sea fishing, and metal mining. Opposite to the literature’s statements, the article’s findings show that the Argentinean extractive pattern does not represent a model of pure neo-develop- mentalist progressivism but an extremely paradoxical accumulation regime where the larger State intervention coexists with the growing presence of foreign private capital and where the dominance of the classic, neoliber- al attributes and the modern neo-extractivist features strongly depends on the economic activities considered.